Targeted Disruption of Mouse Yin Yang 1 Transcription Factor Results in Peri-Implantation Lethality - Donohoe, Mary E. (American Society for Microbiology, 1999)
Yin Yang 1 (YY1) is a zinc finger-containing transcription factor and a target of viral oncoproteins. To determine the biological role of YY1 in mammalian development, we generated mice deficient for YY1 by gene targeting. Homozygosity for the mutated YY1 allele results in embryonic lethality in the mouse. YY1 mutants undergo implantation and induce uterine decidualization but rapidly degenerate around the time of implantation. A subset of YY1 heterozygote embryos are developmentally retarded and exhibit neurulation defects, suggesting that YY1 may have additional roles during later stages of mouse embryogenesis. Our studies demonstrate an essential function for YY1 in the development of the mouse embryo.